Diseño de un Modelo de Gestión de Prevención de Riesgos Laborales para los trabajadores del Relleno Sanitario de Tisaleo, período 2024. - Mayorga Aguagallo, Verónica Elizabeth (2025)
This research aimed to design a management model to prevent occupational risks aimed at workers in the emerging cell of the sanitary landfill in the Tisaleo canton during the 2024 period, which applied a mixed approach combined qualitative and quantitative analyses with a non-experimental descriptive, propositional, field, and documentary methodology. Through surveys, interviews, checklists, and the application of the Hazard Identification, Risk Assessment, and Control Matrix (IPERC), the risk factors associated with the activities carried out by the 7 workers of the landfill were evaluated, including service assistants, collection drivers, and heavy machinery operators. The results highlighted significant hazards such as mechanical injuries, exposure to biological and chemical agents, and ergonomic and environmental risks, with service assistants identified as the most vulnerable group due to their exposure to cuts, leachates, and forced postures. The proposed controls included technical measures such as structural reinforcements, improved signage, engineering controls, administrative measures, and the proper use of personal protective equipment (PPE). Periodic training sessions were also implemented to promote a culture of prevention. In conclusion, the design of the Occupational Risk Prevention Management Manual constitutes a comprehensive tool that organizes procedures and guidelines to ensure a safe work environment.